PENGARUH PENDAPATAN MASYARAKAT TERHADAP PERMINTAAN PELAYANAN KESEHATAN DI KABUPATEN SUMBAWA (Studi Pada RSUD Kabupaten Sumbawa) - Abdul Rahim; Indah Pasari; Marisha Sutanty (Pusat Riset dan Publikasi, 2022)
This study aims to analyze the influence of people's income on the demand for health services at the Sumbawa District Hospital. This type of research is associative research, which aims to determine the relationship between two or more variables. The variables to be examined are people's income as the independent variable (X) and the demand for health services as the dependent variable (Y). The type of data used is quantitative data in the form of respondents' responses in answering the questionnaire given related to the problems studied which were obtained directly from the research respondents. The population in this study were all visitors who requested health services at the Sumbawa City Hospital, totaling 100 people and were taken using the accidental sampling method. Data were collected through questionnaires distributed to respondents to be processed using the SPSS application. Data analysis was performed using simple linear regression analysis techniques, partial hypothesis testing (t test), and determination coefficient test (R2). The results of this study indicate that people's income has a positive and significant effect on the demand for health services at the Sumbawa Regency Hospital. the ability of the community's income variable to influence variations in changes in the variable demand for health services at the Sumbawa District Hospital is 83.4%, while the remaining 16.6% is influenced by other variables outside the scope of this study.